1000 Targeting Sleep in Adults Seeking Treatment for Cannabis Use Disorder. (27th April 2018) - Martin, E L; Schlienz, N J; Herrmann, E S; Budney, A J; Lee, D C; Hampson, A; Smith, M; Leoutsakos, J S; Stitzer, M L; Vandrey, R G
Abstract: Introduction: Sleep disturbance and strange/vivid dreams are among the most-reported symptoms of cannabis withdrawal, and acute cannabis administration has been shown to affect both sleep continuity and architecture. Many individuals with cannabis use disorder (CUD) cite these qualities as contributors to continued use. This research seeks to examine sleep quality in individuals seeking treatment for CUD, and assess the efficacy of a novel hypnotic intervention in increasing rates of abstinence. Methods: 127 adults seeking treatment for CUD and reporting a prior effect of cannabis use on sleep were enrolled in a 12-week clinical trial and randomized to receive either extended-release zolpidem or a placebo. All were provided with computerized therapy modules (cMET/CBT) and abstinence-based contingency management. In-home ambulatory polysomnography (PSG) assessments measured changes in sleep architecture four times over the course of the study. Self-report measures of recent sleep (ISI, DBAS, PSQI) and urine specimens for toxicological testing were collected at bi-weekly study visits. Results: Individuals randomized to receive zolpidem demonstrated higher incidence of abstinence (clean urine) at any point during treatment (33.9% vs. 24.6%) and at end of treatment (27.4% vs. 15.4%). Sleep efficiency in the placebo group significantly decreased and sleep latency increased the first week after quit attempt initiated. Zolpidem attenuated abstinence-induced insomnia, but rebound sleep disturbance was observed after medication washout. Scores on the Insomnia Severity Index were consistently lower in the zolpidem group compared with placebo. Conclusion: Initial effect of cannabis withdrawal on sleep appears to be tempered by nightly zolpidem administration, and higher rates of abstinence in the treatment group were observed. Hypnotic medication may be useful as an adjunct to behavioral treatments of cannabis use disorder to both facilitate initial abstinence and prevent relapse. Research on the type, dose and duration of hypnotic medication use to maximize therapeutic benefit and minimize rebound insomnia following discontinuation is required. Support (If Any): U01-DA031784, T32-DA0720.